2016
DOI: 10.1016/j.neuropsychologia.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Aversive stimuli exacerbate defensive motor behaviour in motor conversion disorder

Abstract: A B S T R A C TConversion disorder or functional neurological symptom disorder (FND) can affect the voluntary motor system, without an organic cause. Functional symptoms are thought to be generated unconsciously, arising from underlying psychological stressors. However, attempts to demonstrate a direct relationship between the limbic system and disrupted motor function in FND are lacking. We tested whether negative affect would exacerbate alterations of motor control and corresponding brain activations in indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 96 publications
(127 reference statements)
4
50
0
Order By: Relevance
“…Our finding of decreased connectivity between the MTL (involved in autobiographical memory) and sensorimotor networks in CD may support theories that repression of stressful or traumatic life events leads to sensorimotor disturbances . It was suggested that psychological defense mechanisms, such as repression or dissociation, are used to ‘block’ patients’ awareness of traumatic memories, leading to the symptoms presented in CD .…”
Section: Discussionsupporting
confidence: 79%
“…Our finding of decreased connectivity between the MTL (involved in autobiographical memory) and sensorimotor networks in CD may support theories that repression of stressful or traumatic life events leads to sensorimotor disturbances . It was suggested that psychological defense mechanisms, such as repression or dissociation, are used to ‘block’ patients’ awareness of traumatic memories, leading to the symptoms presented in CD .…”
Section: Discussionsupporting
confidence: 79%
“…Blakemore et al ,39 for example, found evidence for facilitated manual output force in people with FND-movt while viewing negative IAPS images. Fiess et al 40 reported increased FND symptoms and reduced discomfort threshold after intentional emotion regulation during IAPS exposure.…”
Section: Emotional Processing In Fnd: a Narrative Reviewmentioning
confidence: 99%
“…Altered responsivity to general affective images has been investigated experimentally in individuals diagnosed with disorders that share risk factors and/or clinical characteristics with DS, such as borderline personality disorder (Herpertz, Kunert, Schwenger, & Sass, 1999) and depersonalization disorder (Sierra et al, 2002). Differences in neural activity have also been reported in people with other conversion disorders relative to healthy controls, during processing of affective pictures (Blakemore, Sinanaj, Galli, Aybek, & Vuilleumier, 2016;Fiess, Rockstroh, Schmidt, Wienbruch, & Steffen, 2016). However, to date, only one study has examined more general emotional responding in people with DS in the laboratory.…”
mentioning
confidence: 99%